Kontribusi Supervisi Pendidikan Perspektif Dalam Menjalankan Fungsi-Fungsi Admintrasi Pendidikan - I Wayan Arka (Edukasi: Jurnal Pendidikan Dasar, 2022)
Educational administration is all the techniques and procedures used in the organization of educational institutions in accordance with predetermined policies. This is related to the creation, maintenance of stimulation, and unification of energy in educational institutions in an effort to realize predetermined goals. Educational supervision is part of education administration. The implementation of educational supervision in schools has contributed to efforts to build quality and professional educators.